2022
DOI: 10.14202/vetworld.2022.2890-2895
|View full text |Cite
|
Sign up to set email alerts
|

Effect of follicle-stimulating hormone and luteinizing hormone levels on egg-laying frequency in hens

Abstract: Background and Aim: Gonadotropins, for example, follicle-stimulating hormone (FSH) and luteinizing hormone (LH), are hormones that affect the reproductive process. In hens, optimal levels of FSH and LH can stimulate follicle growth fairly rapidly and thereby increase egg production through follicle development and increased ovulation. Follicle-stimulating hormone acts in the early stages of follicular growth, whereas LH acts on pre-ovulatory follicles. Normal follicular growth is the result of the complementar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…AF18-22) and one gammaproteobacterium ( Methylohalobius crimeensis ). Follicle-stimulating hormone (FSH) and leutinising hormone (LH) concentrations are strongly associated with laying frequency in hens, where both of these hormones are influenced by estradiol concentrations [ 71 , 85 ]. In several human and animal studies, Prevotella and Bacteroides abundances are correlated with estradiol [ 48 , 82 , 106 ], and estradiol has been observed promoting Bacteroides growth [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…AF18-22) and one gammaproteobacterium ( Methylohalobius crimeensis ). Follicle-stimulating hormone (FSH) and leutinising hormone (LH) concentrations are strongly associated with laying frequency in hens, where both of these hormones are influenced by estradiol concentrations [ 71 , 85 ]. In several human and animal studies, Prevotella and Bacteroides abundances are correlated with estradiol [ 48 , 82 , 106 ], and estradiol has been observed promoting Bacteroides growth [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study also detected such a pattern before ovulation in chickens ( Lovell et al, 2005 ). High serum FSH levels were associated with LI ( Prastiya et al, 2022 ). However, the transcript regulation did not always coincide with serum levels, suggesting that FSH might exert certain functions through FSHR in a paracrine manner ( Chu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…This observation may have been a result of a high concentration of prolactin to a level that exceeds the levels required in the egg production process. Prastiya et al (2022) reported that high concentration of prolactin inhibits GnRH secretion which then results in the inhibition of egg production in the birds. However, such is not the case in this study because GnRH concentration in this study was highest in 5 gkg -1 which recorded the lowest FSH concentration.…”
Section: Discussionmentioning
confidence: 99%